Perancangan Aplikasi Akuntansi Sederhana Berbasis Microsoft Excell Di Bahtera Perfumery Solo - Nany, Magdalena; Aggresia Natasa Lede; Yuningsi Septiani Amma; Endang Satyawati (Institut Agama Kristen Negeri Kupang, 2025)
Bahtera Perfumery is a Solo-based perfume brand that offers a wide variety of scents to represent individual personalities. An inventory system has a significant impact on an agency or company. A system that can effectively manage inventory data is needed. With the increasing number of perfume variants and the opening of numerous outlets, Bahtera Perfumery began to feel the need for a simple accounting application that could be used to record incoming and outgoing inventory, sales, and profits in real time. The system was designed for Bahtera Perfumery Solo. The data collection techniques used included observation, interviews, and documentation. The existence of a simple Microsoft Excel-based accounting application that can display daily information on the number of items received, the number of items sold, total sales, cost of goods sold, gross profit, and ending stock value has temporarily met the owner's expectations for financial information for each outlet in the mall. Training is needed to ensure the application can be used immediately. Continued development of the accounting application is needed to ensure it remains relevant to the owner's financial information needs